Tahapan Mendidik Anak dalam Keluarga (Analisis Kitab Shalahul Usrah wa Daurul Abawaini fit Tarbiyah) - Sulaiman Jazuli (IAI DARUL ULUM KANDANGAN, 2023)
This writing aims to find out about the stages that must be known by parents in educating children in the family. This type of research uses library research or literature review. The data analysis technique that the writer uses is content analysis. Through an analysis of the book Shalahul Usrah wa Daurul Abawaini fit Tarbiyah by Habib Umar, it can be concluded that the first stage that must be carried out to educate children in the family starts from choosing a partner or is called the pre-conception stage. The second stage that must be carried out is during pregnancy or is called the prenatal stage and the last stage is the postnatal stage which includes the birth period, the tamyiz period, and the school period.